1959
DOI: 10.1172/jci104002
|View full text |Cite
|
Sign up to set email alerts
|

PULMONARY TRANSCAPILLARY EXCHANGE OF Na24 AND P32-LABELED PHOSPHATE IN PULMONARY EMPHYSEMA*

Abstract: In previous studies it was observed that 5 to 20 per cent of intravenously administered Na24 and P32-labeled phosphate and other electrolytes escaped from the circulation during a single transit through the cardiopulmonary pool (1). The relatively small transcapillary exchange of electrolytes in the lungs as compared with skeletal muscle and certain other viscera was attributed to a lesser permeability of the pulmonary capillaries (1). The fraction of intravascular tracer electrolyte transferred across the pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1971
1971
1971
1971

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Several investigators have studied the transcapillary exchange of small solute molecules and ions in the pulmonary circulation with the single injection indicator diffusion technique (Chinard and Enns 1954, Bauman et al 1957, Rothschild et al 1959, Chinard, Enns and Nolan 1962) . Chinard et al (1954) and Bauman et al (1957) found that only small amounts of "Na passed out from the pulmonary vessels of dogs and healthy humans, respectively, during one single passage of the tracer through the pulmonary vascular bed.…”
mentioning
confidence: 99%
“…Several investigators have studied the transcapillary exchange of small solute molecules and ions in the pulmonary circulation with the single injection indicator diffusion technique (Chinard and Enns 1954, Bauman et al 1957, Rothschild et al 1959, Chinard, Enns and Nolan 1962) . Chinard et al (1954) and Bauman et al (1957) found that only small amounts of "Na passed out from the pulmonary vessels of dogs and healthy humans, respectively, during one single passage of the tracer through the pulmonary vascular bed.…”
mentioning
confidence: 99%